Peningkatan Kesadaran dan Pengetahuan Mitigasi Bencana Siswa MTs Darul Ma’arif Numbay Melalui Sosialisasi dan Simulasi: Pengabdian - Inriyatni Sri Pertiwi Ginting; Fazryani Mazita Torano; Makmum Ashari; Nesliani Paotonan; Mingle A Pistanty; Rian Efendi; Ince Rezky Naing; Fikstif Donal Lintong; Elieser Kulimbang; Rina Ananta Sumawardani Sitepu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to increase awareness and knowledge of disaster mitigation among students of MTs Darul Ma’arif Numbay through socialization and disaster response simulation methods. The background of this activity is the high risk of disasters in Jayapura, while the students' preparedness level is still low based on initial observations. The method used is participatory, starting with interactive socialization about the basic concepts of disaster mitigation, types of disasters that potentially occur in Jayapura, and the importance of readiness and appropriate actions when facing disasters. The material is delivered using visual aids and discussions, followed by a disaster response simulation in the form of an earthquake evacuation scenario involving all students. Evaluation is conducted through observations and question-and-answer sessions before and after the activity. The results show a significant increase in students' understanding of mitigation steps and evacuation procedures, as well as the formation of a disaster-aware culture within the school environment. Students become more prepared and responsive in emergency situations and are able to correctly explain mitigation procedures. Additionally, active student involvement in the simulation also enhances enthusiasm and coordination among school members.